Adaptive control of cluster-based Web systems using neuro-fuzzy models - Zatwarnicki, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
A significant development of Web technologies requires the application of more and more complex systems and algorithms for maintaining high quality of Web services. Presently, not only simple decision-making tools but also complex adaptation algorithms using artificial intelligence techniques are applied for controlling HTTP request traffic. The paper presents a new LFNRD (Local Fuzzy-Neural Adaptive Request Distribution) algorithm for request distribution in cluster-based Web systems using neuro-fuzzy models ofWeb servers in the decision-making process
Keywords: neuro-fuzzy model; request distribution; Web cluster; QoWS